Pengembangan Sistem Informasi Tracer Study Alumni Berbasis Web Menggunakan Metode RUP (Studi Kasus : SMA Suluh Jakarta Selatan) - Mega Isma Juwita; Satrio Agung Wicaksono; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Learning outcomes received by high school graduates will influence the mindset of alumni when studying at a university, based on this, an evaluation of ongoing learning is needed. Suluh High School is a private high school in Jakarta which currently has problems in managing alumni data. The BK teacher as the person in charge of the alumni data was unable to track the existence of alumni as a whole, so the process of contacting alumni to attend the Suluh High School activities was ineffective due to lack of alumni information. Therefore, it is necessary to develop an information system for tracer study alumni who can assist BK teachers in overcoming these problems. The system to be developed is a website-based information system developed using the RUP method, with the average percentage of user acceptance testing test results from the transition stage being 91.4%, so it can be concluded that the developed tracer study information system of alumni can be accepted by users. Keywords: information system tracer study alumni, RUP, User Acceptance Testing, website